Fluctuación estacional del zooplancton en la laguna del Parque Norte, Medellín, Colombia (1997)
ABSTRACT: From April 1991 10 January 1992 nineteen samples of zooplankton and physicho-chemical variables associated with them were measured cach two weeks. These samples were carried out in surface and bottom in only one sampling station with a shower pipe specified for shallow environments. Brachionus plicatilis was the dominant organism with Thermocyclops decipiens Arctodiaptomus dorsalis and Moina sp. The found taxonomic composition is very similar to another eutrofic tropical lakes wilh hard and alkaline waters. Community diversity showed small values and it was more associated with evenness in surface and bottom and it was affected by dominance of B. plicatilis Width niche for this organism and I. decipiens small in both depth. Directional overlap niche index between these two laxa were small too. Cluster analysis for samples showed four groups in surface and bottom organized in accordance with absolute abundance and influenced by I. p/icti/iJ for representing of total zooplankton 56.6% in surface and 70.8% in bottom. For laxa were fonned IwO groups: in first wcre joined ¡hose dominants and abundant laxa and in the second the rare taxa.